The Role of Women as Coaches and Sports Managers: A Study On Challenges And Opportunities - A Literature Review - Nimrot Manalu; Annice Alemina Br Barus; Frili Harmoni Sitompul; Imelda Br Sitepu (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This literature review aims to examine the current status, challenges, and opportunities for women in coaching and sports management positions, synthesizing existing research to identify barriers and potential strategies for advancement. Methods: A systematic review of literature published between 2012 and 2025 was conducted using electronic databases including ResearchGate, ScienceDirect, Taylor & Francis Online, and PubMed. Articles were selected based on relevance to women in coaching and sports management roles, with particular focus on barriers, supports, and advancement strategies. LaVoi and Dutove's ecological model was used as a primary framework for analysis. Results: Despite increased participation of women in sports and sports education programs, women remain significantly underrepresented in coaching and leadership positions across all levels of sport. Women held only 65 of 382 athletic director, commissioner, or other top leadership roles at Division 1 NCAA institutions in 2023. The research identifies multilevel barriers that include organizational factors (inconsistent hiring practices, hypermasculine sport culture), interpersonal factors (lack of mentoring, limited networking opportunities), and individual factors (work-life balance challenges, confidence issues). Successful advancement strategies include mentorship, sponsorship, networking, and building diverse career portfolios. Conclusion: Women in coaching and sports management face persistent barriers embedded in gendered institutional practices. Interventions at multiple ecological levels are required to achieve equity, with organizational change being particularly critical. Formal mentoring programs, intentional networking opportunities, and challenging gendered organizational cultures can create pathways for women's advancement in sports leadership.